Optimization of titanium silicide formation on boron doped silicon using statistical design - Uda Hashim; Abu Hassan Shaari; Burhanudin Yeop Majlis; Sahbudin Shaari (Universiti Kebangsaan Malaysia, 2000)
The effects of first heat treatment temperature, second heat treatment temperature and second heat treatment time on titanium films by measuring the sheet resistance was investigated using statistical design of experiment. Two-level screening experiment with 23 factorial design was used to evaluate three effects in eight combination runs. The analysis of variance revealed that, the second heat treatment temperature was significant and being the main contributing factors to the final sheet resistance of the titanium silicide. The first heat treatment temperature and the second heat treatment time were found not important.